The challenges of the sustainability theme in postgraduate education - Malheiros, Tadeu Fabrício; Pérez, Mario Alejandro; Sampaio, Carlos Cioce; Zuñiga, Christian Henríquez (Revista Brasileira de Pós-Graduação, 2014)
Universities are required to focus on sustainability. Given this challenge, the aim of this paper is to identify and discuss key elements for introducing the sustainability theme to postgraduate programmes in Brazilian universities. The paper, then, applies a set of characteristics that work as key points for the framework of a first draft. As for the curriculum of programmes, the different aspects of the biotic, physical, chemical, cultural and socioeconomic environments must be addressed. As for its modus operandi, the postgraduate programme must be interdisciplinary,looking at critical issues concerning the interface of themes related to sustainability. In order to build alignment and coherence with the theme, it is necessary that the vision, values and principles that are present in this paradigm be progressively made operational.